FACTORS AFFECTING THE DETERMINATION OF ROAD PROJECT PRICES BY LOCAL GOVERNMENT ORGANIZATIONS IN CHANTHABURI PROVINCE - นิลแสง มานิตย์; แวนบอเซอร์ บุญรักษ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research, titled “Factors Affecting The Determination of Road Project Prices by Local Government Organizations in Chanthaburi Province” aims to: 1) examine the level of differences between the allocated budget and the reference price for road construction projects; 2) investigate the factors affecting the determination of the reference price; and 3) propose guidelines for determining the reference price for road construction projects of local administrative organizations in Chanthaburi Province. The sample group consisted of 243 respondents, including directors of public works divisions, engineers, and civil engineering technicians from 81 local administrative organizations. In addition, data from 518 road construction and improvement projects conducted between 2021 and 2025 were collected. The research instruments included questionnaires and the collection of project-level data on allocated budgets and reference prices. Data were analyzed using frequency, percentage, mean, standard deviation, t-test, Chi-square, One-way ANOVA, and content analysis. The research findings revealed that: 1) The difference between the allocated budget and the reference price was mostly within the range of 0% to 5%. Moreover, the difference between the allocated budget and the reference price was significantly related to the type of road at the 0.05 level of statistical significance. 2) Overall, the factors affecting the determination of the reference price were rated at a high level of agreement. Key factors included the qualifications of those responsible for determining the reference price, construction formats/criteria and standards, methods for determining the reference price, the selection of the Factor F value, labor costs, and material and equipment prices. Environmental factors were rated at a moderate level of agreement. Furthermore, several demographic factors significantly influenced differences in respondents’ opinions. The proposed guidelines include developing the capacity of personnel responsible for determining reference prices, improving criteria, calculation methods, and cost data to ensure they are up-to-date, transparent, and consistent with the local context. The reference price determination process should also be enhanced to cover key procedures such as quantity takeoff, cost calculation, and transportation costs, using reliable and regularly updated labor and material price data. In addition, local conditions and environmental factors should be considered to ensure that the reference price accurately reflects actual costs, remains transparent, and can be effectively applied in practice.